2021
DOI: 10.3390/antiox10081230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carotenoids in Haloarchaea Species from Atacama Saline Lakes by High Resolution UHPLC-Q-Orbitrap-Mass Spectrometry: Antioxidant Potential and Biological Effect on Cell Viability

Abstract: Haloarchaea are extreme halophilic microorganisms belonging to the domain Archaea, phylum Euryarchaeota, and are producers of interesting antioxidant carotenoid compounds. In this study, four new strains of Haloarcula sp., isolated from saline lakes of the Atacama Desert, are reported and studied by high-resolution mass spectrometry (UHPLC-Q-Orbitrap-MS/MS) for the first time. In addition, determination of the carotenoid pigment profile from the new strains of Haloarcula sp., plus two strains of Halorubrum teb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 61 publications
(77 reference statements)
4
20
0
2
Order By: Relevance
“…2). These results are in agreement with previous reports using carotenoid extracts of halophilic archaea from various origins (Flores et al 2020;Hegazy et al 2020;Hou and Cui 2018;Lizama et al 2021;Mandelli et al 2012;Squillaci et al 2017;Yatsunami et al 2014). ,490,523 705.5 673.5,619.4,579.1,540.3,487.4,457.6,439.1,394.5,315.2 2 BR 12.80 468,497,530 741.7 723.4,683.7,664.5,646.0,537.9,484.2,459.0,425.2,386.5,346.1,314.2 3 BR 14.44 468,496,530 741.3 648.5,593.5,561.8,501.4,450.8,406.6 4 BR 15.84 466,495,528 741.2 689.4,656.4,632.4,606.4,577.4,560.0,523.9,470.3,…”
Section: Antioxidant Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…2). These results are in agreement with previous reports using carotenoid extracts of halophilic archaea from various origins (Flores et al 2020;Hegazy et al 2020;Hou and Cui 2018;Lizama et al 2021;Mandelli et al 2012;Squillaci et al 2017;Yatsunami et al 2014). ,490,523 705.5 673.5,619.4,579.1,540.3,487.4,457.6,439.1,394.5,315.2 2 BR 12.80 468,497,530 741.7 723.4,683.7,664.5,646.0,537.9,484.2,459.0,425.2,386.5,346.1,314.2 3 BR 14.44 468,496,530 741.3 648.5,593.5,561.8,501.4,450.8,406.6 4 BR 15.84 466,495,528 741.2 689.4,656.4,632.4,606.4,577.4,560.0,523.9,470.3,…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…However, bacterioruberin was the predominant carotenoid accumulated by the three haloarchaea strains. Such dominance has also been reported in several previous studies (De La Vega et al 2016;Flores et al 2020;Hou and Cui 2018;Lizama et al 2021;Montero-Lobato et al 2018;Squillaci et al 2017;Yatsunami et al 2014). In fact, bacterioruberin is the main C 50 carotenoid component responsible for the color of the red archaea of the class Halobacteria (Giani et al 2019).…”
Section: Carotenoid Profile Of Haloarcula Sp Bt9supporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, novel species under the genus Halorubrum, isolated from South Korea, produced C 50 carotenoid (bacterioruberin), having a strong antioxidant activity (Hwang et al, 2022). Likewise, carotenoids from novel Haloarcula sp., and Halorubrum sp., strains were isolated from the Atacama Desert (Lizama et al, 2021). Large-scale whole genome (n = 68) analysis suggested that haloarchaea has a wide diversity of carotenoid biosynthetic genes (Serrano et al, 2022), suggesting that haloarchaeal species could be a reservoir of carotenoid derivatives.…”
Section: Biotechnological Significance Of Haloarchaeamentioning
confidence: 99%
“…In vivo: not reported In vitro: antioxidant, anti-inflammatory [55]; antiviral and anti-cancer activity [65] Cholinesterase [66], cyclooxygenase-2 [67], α-glucosidase, α-amylase, and pancreatic lipase [68] inhibition Beneficial effects on sperm cell viability [69] Antimicrobial activity against pathogenic bacteria and fungi [54,70,71]…”
Section: In Vivo/in Vitro Activitymentioning
confidence: 99%